The role of DCDC2 genetic variants and low socioeconomic status in vulnerability to attention problems - Riva, Valentina; Marino, Cecilia; Giorda, Roberto; Molteni, Massimo; Nobile, Maria (European child & adolescent psychiatry, 2015)
Both genetic and socio-demographic factors influence the risk for behavioral problems in the developmental age. Genetic studies indicate that shared genetic factors partially contribute to behavioral and learning problems, in particular reading disabilities (RD). For the first time, we explore the conjoint role of DCDC2 gene, an identified RD candidate gene, and socioeconomic status (SES) upon behavioral phenotypes in a general population of Italian children. Two of the most replicated DCDC2 markers [i.e., regulatory element associated with dyslexia 1 (READ1), rs793862] were genotyped in 631 children (boys = 314; girls = 317) aged 11–14 years belonging to a community-based sample. Main and interactive effects were tested by MANOVA for each combination of DCDC2 genotypes and socioeconomic status upon emotional and behavioral phenotypes, assessed by Child Behavior Check-List/6–18. The two-way MANOVA (Bonferroni corrected p value = 0.01) revealed a trend toward significance of READ1(4) effect ( F = 2.39; p = 0.016), a significant main effect of SES ( F = 3.01; p = 0.003) and interactive effect of READ1(4) × SES ( F = 2.65; p = 0.007) upon behavioral measures, showing higher attention problems scores among subjects ‘READ1(4+) and low SES’ compared to all other groups ( p values range 0.00003–0.0004). ANOVAs stratified by gender confirmed main and interactive effects among girls, but not boys. Among children exposed to low socioeconomic level, READ1 genetic variant targets the worst outcome in children’s attention.